Dialogues between sociology and history - Melo, Sabrina Fernandes (2013)
BOURDIEU, Pierre; CHARTIER, Roger. O sociólogo e o historiador. Belo Horizonte: Autêntica, 2011, 134p. Tradução de Guilherme João Teixeira, com a colaboração de Jaime Clasen.